Determinan Budaya Organisasi dan Pelatihan dalam Peningkatan Kinerja Karyawan dalam Perspektif Ekonomi Islam - Hairani, Tuti (ITB AAS INDONESIA Surakarta, 2023)
This research is motivated by the trend of declining employee performance. This study aims to identify and analyze the Determinants of Organizational Culture and Training in Improving Employee Performance in the Perspective of Islamic Economics. This research is a descriptive research with a quantitative approach. The sample in this study were 96 employees of Bank Syariah Indonesia which were taken by random sampling. Data collection techniques by way of observation, questionnaires and questionnaires. The instruments used have been tested for validity and reliability. The collected data were analyzed using the classical assumption test and multiple linear regression with SPSS tools. The results of this study indicate that 1) Organizational culture has a positive and significant effect on employee performance in an Islamic economic perspective, 2) Training has a positive and significant effect on employee performance in an Islamic economic perspective, and 3) Organizational culture and training have a positive and significant effect on employee performance. significantly to employee performance in the perspective of Islamic economics. The findings of this study reveal that if Bank Syariah Indonesia wants to improve employee performance, it must improve organizational culture and training.